Athletes with versus without leg amputations: Different biomechanics, similar running economy - Beck, O.; Grabowski, A. M. (Exercise and Sport Sciences Reviews, 2019)
Athletes with transtibial amputations use carbon-fiber prostheses to run. Compared with biological legs, these devices differ in structure and function, and consequently yield affected leg running biomechanics that are theoretically more economical than those of nonamputees. However, experimental data indicate that athletes with unilateral and bilateral transtibial amputations exhibit running economy values that are well within the range of nonamputee values.